Urban Growth-Driven Land Use and Climate Dynamics: Assessing Changes in Dhaka City (1990–2022) (Jagannath University Journal of Life and Earth Sciences, 2025)
Since 1990, Dhaka has experienced rapid, unplanned urban expansion, profoundly altering land-use patterns and intensifying local climate extremes in one of the world’s most densely populated megacities. This study aims to quantify three decades of land use and land cover (LULC) changes and evaluate their associated impacts on land surface temperature (LST), near-surface air temperature, and rainfall, with a view to informing climate-resilient urban planning. Landsat 5 TM (1990) and Landsat 9 OLI-2/TIRS-2 (2022) imagery were analyzed using ArcGIS and ERDAS Imagine to classify built-up areas, vegetation, bare land, and water, achieving high accuracy (κ = 0.93). LST was estimated using radiometric calibration, NDVI-based emissivity correction, and the mono-window algorithm, while long-term climate data from the Bangladesh Meteorological Department supported trend analysis. Findings reveal a 41.15% increase in built-up area, largely at the expense of vegetation (–31.02%), resulting in a 4.87 °C rise in peak LST and a 71 mm increase in annual rainfall. Strong positive correlations (|r| ≥ 0.99) show that each 1% gain in built-up land adds approximately 0.12 °C to LST and enhances convective precipitation, whereas vegetation loss exerts a cooling and drying effect. These dynamics are exacerbating urban-heat-island intensity, disrupting seasonal rainfall, and increasing flash-flood and health risks. To counteract these effects, the study recommends vertical urban densification, conservation of wetlands and green belts, and integration of green–blue infrastructure alongside high-resolution remote sensing and climate modeling for adaptive urban policy and planning.Jagannath University Journal of Life and Earth Sciences, 10 (2): 153-177 (December 2024)